Ascent of the mountain, flight of the dove : an invitation to religious studies - Novak, Michael, 1933- (Harper & Row, 1971)
The essence of Ascent of the Mountain, Flight of the Dove remains intact: its vision of religious studies as sustained refl ection on our lifelong voyage to discover who we are. The story we choose for ourselves, the story we live, can sacralize or secularize our lives and our world by the way in which we choose to relate to it. With this awareness of the story dimension of life, Ascent of the Mountain, Flight of the Dove opens us to awe, reverence, and wonder at the risks and possibilities of human freedom.